Assessment of transient effects of alternative nitrogen sources in continuous cultures of Arthrospira sp. using proteomic, modeling and biochemical tools. (November 2018) - Sachdeva, Neha; Giambarresi, Giuseppe; Poughon, Laurent; Cabrera, Juan Carlos; Leroy, Baptiste; Lasseur, Christophe; Dussap, Claude-Gilles; Wattiez, Ruddy
Graphical abstract: Highlights: Transitional-continuous feeding of ammonium-nitrate. Modified cultivation approach avoided inhibitory effects of ammonium. Comprehensive biochemical, proteomic and photosynthetic profiling of biomass. Light-energy-transfer model used for prediction of productivities. 95 ± 2% match was observed between the experimental and simulated productivities. Abstract: The ability of cyanobacterium Arthrospira sp. to assimilate waste nitrogen sources (ammonium and urea) makes it an important candidate for wastewater management. The aim of this work was to evaluate a cultivation approach based on continuous-transitional-feeding regime (nitrate-ammonium-nitrate) in a photobioreactor to assess the effects of ammonium salts on Arthrospira sp. PCC 8005 metabolism. Using a comprehensive biochemical, proteomic and stoichiometric profiling of biomass, this study demonstrated that the proposed cultivation approach could increase the proteins and pigments yields by 20–30%, compared to the respective yields obtained from wild-type Arthrospira sp. strain A light-energy-transfer model was used to predict the biomass and oxygen productivities of Arthrospira sp. cultivated under transitional-feeding regime. 95 ± 2% match was observed between the experimental and simulated productivities. This study thus opened new avenues for use of ammonium rich wastewater for commercial production of high value pigments, biofuel and bioplastics using Arthrospira sp.